Childhood Masturbation: A Case Report and Literature Review for Treatment - Lestari, Ade Febrina; Sitaresmi, Mei Neni; Ridhayani, Firda (Academic Hospital Journal, 2023)
Background: Masturbation is normal sexual behavior. However, masturbation in childhood is rarely discussed in the research. Childhood masturbation or gratification disorder, is characterized by self-stimulation of genitalia in prepubescent children. However, childhood masturbation often stops if the child is distracted, and spontaneous recovery within two years in most cases Generally, no drug therapy is required for childhood masturbation unless it is very frequent or excessive and it affects the daily functionality of the child. Regarding the treatment of childhood masturbation, we highlight the fact that evidence-based therapy for childhood masturbation is lacking due to unclear standard guidelines on it. We need a path of therapy that can help doctors in the management of childhood masturbation. Case: Here we reported two cases of excessive childhood masturbation from a 3-year-old and a 10-month-old female patient who were brought by their mother to the outpatient clinic pediatric, Academic Hospital, Universitas Gadjah Mada, Indonesia, with a complaint of stretching by flexing the legs and rubbing on her genital part Risperidone as one of the drug therapies for this case and present a good outcome. Additionally, this article also provides literature reviews on childhood masturbation treatment that may guide clinicians in its evaluation and management. Conclusion:  We conclude that behavioral treatment is the common strategy for childhood masturbation.  The treatment, as well as behavioral and drug therapeutic strategies, should be considered to achieve an effective outcome.